EXPLORING THE USE OF L1 IN ALGERIAN EFL EDUCATION: A QUALITATIVE INVESTIGATION AMONG FIRST-YEAR SECONDARY SCHOOL TEACHERS IN BATNA - Saida TOBBI (Universitaria Publishing House, Craiova, 2024)
The aim of this study is to delve into the utilization of the mother tongue (Arabic) by English as a foreign language (EFL) teachers in the Algerian context. Employing a qualitative approach, we conducted semi-structured interviews and observed nine first-year secondary school teachers across six schools in Batna city center, accumulating a total observation time of 16 hours. Analysis of both the interviews and classroom observations reveals that teachers primarily use L1 as an organizational and affective tool and occasionally as an academic one. In the former, it serves to manage the classroom, redirect the learners towards the task at hand, reproach them for not possessing prior knowledge, and express teachers' frustration. In the latter, it is employed for explaining new vocabulary items and grammar rules, clarifying concepts and instructions, checking learners' understanding, giving feedback, and bridging cultural gaps. Additionally, our findings indicate that L1 is used cautiously and only when deemed necessary, as teachers believe that its overuse hinders learning the target language (TL) and reinforces undesirable cognitive habits such as thinking in Arabic when using English.